Based on network pharmacology to explore the molecular mechanisms of astragalus membranaceus for treating T2 diabetes mellitus - Li, Jie (Ann Transl Med, 2019)
BACKGROUND: Astragalus membranaceus refers to a type of traditional Chinese medicine (TCM) used to treat type 2 diabetes mellitus (T2DM), whereas its molecular mechanism remains unclear. In the presented study, network pharmacology was performed to analyze the molecular mechanism of astragalus membranaceus against T2DM. METHODS: First, we found common targets of astragalus membranaceus and disease, protein-protein interaction (PPI) network was built by String, and then key targets were screened from these common targets by topological analysis. Subsequently, common targets were introduced into DAVID to achieve the results of gene ontology (GO) and KEGG enrichment analysis. The therapeutic effect of astragalus was observed, and several key targets were verified by an animal experiment. RESULTS: First, 13 key targets (EGFR, KDR, SRC, ERBB2, FYN, ESR1, AR, HSP90AA1, PTGS2, ABCG2, AB1, MMP2, and CYP1) were found by topological analysis. Then, the results of GO and KEGG suggested that the anti-diabetes effect of astragalus membranaceus was strongly associated with the activation of receptor protein tyrosine kinase (RPTK). The results of animal experiments revealed that astragalus could enhance the morphology of rat pancreas and up-regulate the expression of tyrosine receptor. CONCLUSIONS: In brief, 13 key targets were found in this study, and astragalus membranaceus was found up-regulating insulin signaling pathways by improving the activity of casein kinase, regulating lipid metabolism, and enhancing insulin resistance to treat T2DM. The present study lays a basis for subsequent experimental research and broadens the clinical application of astragalus membranaceus.